CT-derived adipose tissue characteristics and TAVI all-cause mortality and complications: a systematic review - Matej Pekar; Piotr Branny; Otakar Jiravsky; Radim Spacek; Jan Alexander Mohr; Ivan Ranic; Bogna Jiravska Godula; Alica Cesnakova Konecna; Marek Kantor; Jan Hecko; Radek Neuwirth; Libor Sknouril; et al. (European Journal of Medical Research)
Abstract Transcatheter Aortic Valve Implantation (TAVI) has revolutionized severe aortic stenosis treatment, but risk stratification remains challenging. This systematic review examined the association between computed tomography (CT)-derived adipose tissue parameters and TAVI outcomes. We searched major databases for studies on visceral (VAT), subcutaneous (SAT), and intramuscular (IMAT) adipose tissue parameters and post-TAVI outcomes. Fourteen studies (9692 patients) were included. Higher SAT area/volume was consistently associated with better survival (5 studies, HR range: 0.83–2.77, p < 0.05). Lower SAT and VAT density also correlated with better survival (5 and 4 studies, respectively, HR range: 1.31–1.46, p < 0.05). VAT area showed mixed results. A VAT:SAT ratio < 1 was associated with better cardiovascular outcomes in one study. Lower IMAT index correlated with shorter hospital stays in a single study. This review reveals complex relationships between adipose tissue parameters and TAVI outcomes. Lower adipose tissue density and higher subcutaneous adiposity were most consistently associated with better outcomes. These findings suggest that detailed analysis of adipose tissue characteristics may enhance risk stratification in TAVI candidates.